Analyzing energy flexibility by demand response in a Finnish district heated apartment building - Yuchen Ju and Juha Jokisalo and Risto Kosonen and Ville Kauppi and Philipp Janßen (E3S Web of Conferences, 2021)
In order to realize the vision of climate neutrality, the proportion of renewable sources is increasing in the energy system. To accommodate the energy system, demand response (DR) has been established to make the building energy use flexible. This study aims to investigate the effect of DR actions on energy flexibility in a Finnish district heated apartment building. The rule-based control algorithm was applied for the DR control of space heating based on the Finnish dynamic hourly district heat price. This research was implemented with the validated dynamic building simulation tool IDA ICE. The obtained results show that price fluctuation impacts the DR control and further affects the amount of charging and discharging energies. February has the maximum hourly district heat price with the largest variation, which results in the maximum charging energy of 968 kWh during a single charging period being close to the heat storage capacity of a fully mixed 28 m3 water tank with ? T of 30 K. The studied demand response control can significantly shape the heating power demand of the buildings and increase the flexibility of the energy use.